Implications of immunotherapy with high-dose glatiramer acetate in acute phase of spinal cord injury in rats. (2nd January 2019) - Askarifirouzjaei, Hadi; Khajoueinejad, Leila; Salek Farrokhi, Amir; Tahoori, Mohammad-Taher; Fazeli, Mehdi; Tiraihi, Taki; Pourfathollah, Ali Akbar
Abstract: Objective: Recently, many researches with different viewpoints have focused on application of immunotherapy agents in treatment of spinal cord injury (SCI) according to neuroprotective results in some neurodegenerative disease. Glatiramer acetate (GA) is the most commonly used drug for Multiple sclerosis (MS) patients that exerts an immunomodulatory effect against Myelin basic protein (MBP) antigen. Materials and methods: High-dose (2mg/kg) treatment of GA for 28 consecutive days after SCI was compared with its low-dose (0.5 mg/kg) treatment, SCI control and Sham control rat groups. Results: High-dose GA group had significantly worsened outcome in standard functional recovery evaluation test (BBB) 12 weeks after SCI compared to SCI control and low-dose GA groups, which was confirmed by augmented spinal cavity volume and reduced ventral horn motor neurons in high-dose GA group; however, there was no significant difference between low-dose GA and control SCI group. In addition, proliferation test performed on lymphocytes from spleen and lymph nodes one week after SCI showed that high-dose GA injection has more significant effect on Division Index (DI) in response to MBP stimulation compared to low-dose GA and control SCI groups, which was associated with significant increase in IFN-γ, IL-4, and IL-17A secretion. Conclusion: Along with confirmation of deleterious aspects of autoimmunity resulting from autoreactive lymphocytes against myelin antigens in SCI, this study has shown that high-dose immunotherapy using GA, especially in acute phase after SCI, overwhelms any neuroprotective effect of adoptive immune system.